(untitled) (Revista de História da UEG (REVHIST), 2021)
With his work we intend to investigate the ideological nuances that underlie the emergence of what we are denominating a new “new right” in Brazil, which is the one constituted by the actors who make up the political action frameworks today, but which is projected towards a horizon of more distant future, given the generation that integrates, namely, the youth of today. For that, we used the data from the research project named “Projeto Residente: Observatório das relações entre jovens, história e política na América Latina”, which has among its objectives to seek elements to base reflections on the historical and political culture of young Latin Americans. For this proposal, the objective was to understand how the groups to the right of the political spectrum in our material are characterized; how young people identified – from the use of the political compass – as “authoritarian right” and “democratic right” position themselves in relation to some political, economical and social themes; besides what are the means of political action that these young people declare to integrate. The results indicate that long duration elements are related to the positioning of young people. Most of them tend to have a democratic position. The general profile of the young people on the right is men, middles class, religious, nationalist and attached to the family institution. The rights, as we were able to attest, are quite plural, and the positioning within this political spectrum can vary, despite the strong attachment to traditional and hierarchical institutions. Keywords: political position. Political culture. Young. Right.